Innovating innovation @tk - Chesbrough, Henry (SAGE Knowledge. Cases., 2018)
This case shows how ThyssenKrupp (tk) has altered its innovation process in recent years. CEO Heinrich Hiesinger has brought in a former colleague from Siemens, Reinhold Achatz, to lead a transformation of the R&D function at the company. With tk's roots over 200 years old and its highly divisionalized organization structure, Achatz had to be thoughtful and strategic about how to manage this change. At the same time, tk needed to boost its organic growth, which put pressure on the organization to move fast. The case follows projects through the new innovation process and invites students to place new projects into the proper place in the innovation process.